WHAT WORDS SHOULD WE TEACH? EXPLORATION INTO VOCABULARY PROFILER - Gusti Astika (Center of Language and Cultural Studies [CLCS], 2017)
Students learning English as a foreign language are often frustrated when they have to cope with new words. The teacher’s task in teaching vocabulary seems equal to the student’s learning burden when it comes to decide which words to introduce and how to select words that the students actually need to learn. This article proposes that Vocabulary Profiler (www.lextutor.ca) can be utilized to profile the vocabulary in a textbook to produce word frequency . An English textbook with 21,577 words was selected for analysis with the Vocabulary Profiler. The output shows high and low frequency word groups that can be used as bases for vocabulary selection in teaching. In addition, the output provides information about negative vocabulary and token recycling index, an indicator of text comprehensibility. Although this article sampled a textbook for use in Indonesian contexts, the ideas might be of interest to EFL teachers in other countries.